Ø¨Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ø±Ø§ÙŠØ© â€Ø³ÙˆÙƒØ§Ø¨ÙˆÙ…ÙŠâ€Ž â€Ž Ø¥Ø¯Ø§Ø±Ø© Ø¨Ø±Ù†Ø§Ù…Ø¬ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ø·Ù„Ø¨Ø© ÙÙŠ Ø§Ù„Ø³Ù†Ø© Ø§Ù„Ø£ÙˆÙ„ - Rasyad, M. Ashadi; Lestari, Risza Putri; Rahim, Fitri Kurnia (IAIN Salatiga, 2019)
This study describes the management of Arabic language learning programs for First Year Students at STIBA Ar Rayyah Sukabumi. The output produced has high Arabic skills and competencies. This is motivated by the existence of a one-year language preparation program in the first year. This study aims to describe the planning, organizing, implementing and overseeing the management process of the Arabic language learning program for First Year Students at STIBA Ar Rayyah Sukabumi. This study uses a qualitative research methodology with a type of case study research. The results of this study indicate that 1) the planning of the learning program is based on musyawaroh with several stages, namely observation, coordination meetings, compiling work programs, implementing programs, 2) organizing the program well structured, and policy holders is idaroh 'ulya, 3) Program implementation through language acquisition, atta'allum atta'awuni (mutual cooperation system), regeneration, bi'ah lughowiyah (language environment), 4) program supervision is direct by idaroh 'ulya.